Simulasi Sebaran Temperatur Pelat Logam Tipis Besi dan Kuningan Berbasis Matlab - Iman Noor; Andry Fitrian (Navigation Physics : Journal of Physics Education, 2020)
Simulating the temperature distribution of iron and brass metal thin plates based on matlab has been performed. This simulation aimed to study iron plate and brass plate conductors of the temperature distributionbased on conduction mechanism on cartesian coordinate system. The initial temperature in all parts of the thin plate is room temperature, except at left side and right side of the plate is 100 oC. Through numerical calculation of heat conduction equation by Finite Difference Method, we got that the temperature at center thin plate for 10 second is 63,26oC and 62,08 oC for brass thin plate and iron thin plate, respectively.